The Effect of Influencers and Social Media Influencers on Purchase Intention of Pixy Products Through Source Characteristics - Dheanda Maurizta Chairunnisa; Widiartanto Widiartanto; Ari Pradhanawati (International Journal of Social Service and Research (IJSSR), 2023)
Technological developments make everything easy, one of which is accessing information on social media, namely Youtube. For some people, this is used by creating video content that presents various kinds of information, one of which is in the form of make-up products in the beauty sector, which are also called beauty influencers. Suhay Salim is a beauty influencer who uses his YouTube social media to review beauty products, one of which is PIXY products. The purpose of this study was to determine whether or not influencers and social media influencers had influence on purchase intention of PIXY products through a source characteristics study on influencer Suhay Salim. This researcher used the method of distributing questionnaires to 150 respondents who knew Suhay Salim using path analysis techniques and concluded that influencers and social media influencers had an influence on source characteristics with the results of the coefficient of determination from the calculation results of 2,370 and 3,021.